VideoHandles: Searching through action camera videos by replicating hand gestures. (May 2015) - Knibbe, Jarrod; Seah, Sue Ann; Fraser, Mike
Abstract: We present a detailed exploration of VideoHandles, a novel interaction technique to support rapid review of wearable video camera data by re-performing gestures as a search query. The availability of wearable video capture devices has led to a significant increase in activity logging across a range of domains. However, searching through and reviewing footage for data curation can be a laborious and painstaking process. We showcase the use of gestures as search queries to support review and navigation of video data. By exploring example action-camera footage across a range of activities, we propose two video data navigation styles using gestures: prospective gesture tagging and retrospective gesture searching . This paper builds on our earlier VideoHandles work, reporting details of our interaction design and implementation, and presenting two additional evaluations. We demonstrate that VideoHandles is a viable interaction technique, returning promising results in its prototype form. Abstract : Graphical abstract: Abstract : Highlights: Current video review techniques are unsuitable for action-camera video. We explore example action-cam footage and highlight usage styles. We propose 2 video navigation styles; prospective tagging and retrospective search. We detail a technique to support action-camera video search by replicating gestures.